Dream&Tell - an automated multimedia story maker (A) - Lim, Justina Li Ying (Nanyang Technological University, 2022)
With the advent of new technologies, gone are the days of paper as more people consume their content digitally. This phenomenon has led to a new wave of digital publishing houses that are re-innovating the way people read today. No longer static, the eBook has evolved to one that is interactive. The proliferation of eBooks is seen in the education sector alongside the rising demand for eBooks for e-learning. However, the supply of eBook creators for those without design and technical backgrounds is limited. Thus, Dream&Tell caters to independent children's books authors and teachers – those who lack the design and tech experience – who want to create interactive stories for children.